A study of the kinetics and the effect of trace elements on mixed anaerobic fermentative biogas production by ternary quadratic general rotary unitized design - Chenxiao Zhang; Jing Lian; Zongshan Jiang; Jianbo Guo; Yankai Guo; Chenye Gou (Biotechnology & Biotechnological Equipment, 2016)
In this study the effect of trace elements on methanogenesis was investigated during mixed anaerobic fermentation using a single-factor experiment in the present study. The most effective concentrations of Fe0, Fe2+, Co2+ and Ni2+ that were added were 1500, 250, 0.3 and 0.6 mg/L, respectively. The optimal trace element combination was 0.58 mg/L Ni2+, 1200 mg/L Fe0 and 0.34 mg/L Co2+ by the ternary quadratic general rotary unitized design method. The degree of influence exerted by trace elements on the cumulative methane yields decreased in the order of Ni2+, Fe0 and Co2+, and the maximum CH4 yield was 241.6 mL/g volatile solids (VS), according to a regression equation. The non-dissolved organic carbon hydrolytic process showed a good fit with the first-order kinetic model. The maximum value of CH4 was 312.87 mL/g VS. Compared to the control, the bioconversion efficiencies of CH4 and CO2 production increased by 36.76% and 74.50%, respectively, at the optimal trace element combination. The obtained results provide new knowledge for improvements in the efficiency of anaerobic fermentation biogas production.